Clinical Practice Guidelines for the Treatment of Metastatic Renal Cell Carcinoma: Today and Tomorrow - Molina, Ana M. (AlphaMed Press, 2011)
In the U.S. and Europe, clinical practice guidelines for metastatic renal cell carcinoma have undergone several revisions as a result of the introduction of molecular-targeted therapies. Recently, the National Comprehensive Cancer Network (NCCN) and the European Association of Urology (EAU) published updated guidelines to reflect these new treatment approaches that provide greater efficacy and better tolerability than the previous standard of care, cytokine therapy with interleukin-2 or interferon-α. Recommendations are classified by line of therapy, Memorial Sloan-Kettering Cancer Center risk level for survival, and level of evidence. Although many similarities exist, levels of evidence between the NCCN and EAU guidelines have differing designations and definitions, and timing of updates varies. New research developments, such as identification of effective combinations of targeted agents, optimal regimens for sequential therapy, newly designed targeted agents, benefits in special populations, and identification of additional prognostic factors and biomarkers, will prompt continued updates and refinements of today's clinical practice guidelines, with the goal of providing physicians with the most up-to-date clinical consensus upon which to base treatment decisions. Because clinical trial populations may not represent real-life patient populations, recommendations should serve only as a guide and must be tailored to the needs of each patient.